(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Background:The causes of sudden cardiac death are undetected despite detailed postmortem examination, histological examination and toxicological analysis leading to negative autopsy in some cases. The present study is carried out with a view to evaluate the victims of sudden cardiac death (SCD) brought for medicolegal autopsy. Material and methods: The present cross sectional study included 74 cases of sudden cardiac death within 24 hours with history of chest pain or known ischaemic heart disease brought for medicolegal autopsy. During the autopsy, heart and coronaries were dissected to find out any pathology and the subjected for histopathological examination.Results: The victims of SCD were mostly males (85.1%) with peak incidence in older ages above 60 years (41.9%). Almost 84% of the victims had survival period of less than 6 hours. Left anterior descending artery (64.9%) was the commonest coronary artery involved with atherosclerosis. Most of the victims had double vessel block with 71.6% had coronary narrowing exceeding 75% stenosis. There was statistically significant positive correlation between the coronary block and the age of the victim of sudden cardiac death (p=0.007).Conclusion: Careful and detailed autopsy can beconducted in SCD to find out its cause.